A Novel Modified Turn-on Angle Control Scheme for Torque-ripple Reduction in Switched Reluctance Motor - Milad Dowlatshahi; Mehrdad Daryanush (Institute of Advanced Engineering and Science, 2016)
In recent years, Switched Reluctance Motors (SRM) have been dramatically considered with both researchers and industries. SRMs not only have a simple and reliable structure, but also have low cost production process. However, discrete torque production of SRM along with intensive magnetic saturation in stator and rotor cores are the major drawbacks of utilizing in variety of industrial applications and also causes the inappropriate torque ripples. In this paper, a modified logical-rule-based Torque Sharing Function (TSF) method is proposed considering turn-on angle control. The optimized turn-on angle for conducting each phase is achieved by estimating the inductance curve in the vicinity of unaligned position and based on an analytical solution for each phase voltage equation. Simulation results on a four-phase switched reluctance motor and comparison with the conventional methods validates the effectiveness of the proposed method.